Efecto inhibitorio in vitro del aceite esencial de las hojas de minthostachys mollis (muña) sobre enterococcus faecalis ATCC 29212 - Alaba Castañeda, Wesley (2013)
The objetive of the present experimental study was to determine and compare the inhibitory effect in vitro from IKI 2% solution and Minthostachis mollis (Muña) essential oil, against strains of Enterococcus faecalis. The susceptibility test was made using the dissemination in discs method or Kirby-Bauer method. Seven plates were used containing culture mediun Muller-Hinton, where the Enterococcus faecalis strain were sown. The discs with 2 different concentrations of Minthostachis mollis essential oil 50% and 100% and IKI 2% solution were placed in the plates. These were incubated at 37°C measured halos with a rule after 24, 48 and 72 hours. 24 hours later, all discs presented inhibition halos, the biggest was produced by Minthostachis mollis essential oil 100% pure. And the smallest was shown by IKI 2% solution. The conclusion of this study in that Minthostachis mollis (Muña) essential oil 100% pure, has better inhibitory in vitro effect againts Enterococcus faecalis that IKI 2% solution and etanolic 50% Minthostachis mollis essential oil.